Factors Impacting Discharge Destination From Acute Care for Patients With Traumatic Brain Injury: A Systematic Review. Issue 1 (January 2018) - Recker, Alexander; Putt, Rachelle; Broome, Elizabeth; Farrell, Anne; McCallum, Christine; Paz, Jaime
Abstract : Purpose: The purpose of this systematic review was to identify factors likely to impact discharge destination from acute care in patients with a traumatic brain injury (TBI). Methods: PubMed, CINAHL, Web of Science, Scopus, and ProQuest databases were systematically searched in November 2016 according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Guidelines. Inclusion criteria consisted of patients diagnosed with TBI in the acute care setting, descriptive and quantitative factors impacting discharge destination, and publishing dates from 2007 to 2016. Results: Nine articles were included in this review and demonstrated good validity determined by the Evidence Based Library and Information Practice Critical Appraisal Checklist. Findings suggest that increased length of stay, high injury severity, and older age have the greatest effect on discharge destination. These factors increased the likelihood of discharge to post–acute care, including settings such as skilled nursing, inpatient rehabilitation, outpatient rehabilitation, or home health services. Conclusion: This review presents quantitative information related to factors likely to impact the corresponding discharge destination for patients with TBI. Clinically, professionals may consider this information when determining discharge destination for a patient with TBI following an acute care hospital stay.